EVALUASI KEMAMPUAN LITERASI DIGITAL SISWA SMP KRISTEN CITRA BANGSA KUPANG DALAM MEMBEDAKAN INFORMASI FAKTUAL DAN HOAKS DI MEDIA SOSIAL TIKTOK - Bonevasius malo; Diana Yanni Ariswati Fallo; Yonly A. Benufinit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Bonevasius Mario Malo, 2025. Evaluation of the Digital Literacy Skills of Citra Bangsa Kupang Christian Junior High School Students in Differentiating Factual Information and Hoaxes on Social Media. Informatics Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa Kupang University. Supervisors: Ms. Diana Y.A. Fallo, S.Kom., M.T. and Mr. Yonly A. Benufinit, S.Kom., M.T. This study aims to assess the digital literacy skills of Citra Bangsa Kupang Christian Junior High School students in differentiating factual information from hoaxes on social media and identify the factors influencing this. This study used a quantitative approach with descriptive methods. Data were collected through tests (pre-test and post-test) and questionnaires. The pre-test was conducted before the digital literacy socialization activity to measure students' initial abilities, while the post-test was administered after the socialization to determine their improvement. The results of the study showed a significant improvement in students' digital literacy skills. The average pre-test score of 74.50 increased to 92.63 in the post-test. Furthermore, the questionnaire results from 40 respondents yielded an average percentage of 71.81%. These findings indicate that digital literacy socialization has a positive effect on improving students' critical thinking skills in assessing and verifying information on social media. Therefore, digital literacy socialization activities play a crucial role in developing students who are intelligent, critical, and responsible in their use of social media.